FUNGSI TINDAK TUTUR PENGAJAR BIMBEL DALAM STATUS FACEBOOK TENTANG PENYAMBUTAN TAHUN BARU MASEHI - Desi Afrianti (Puitika, 2017)
This research studies about discourse usedby teachers in Ganesha Operation (GO) Sumbar in their facebook’s status about welcoming new year of 2014. It is interesting to be analyzed because every discoursehas one function. Moreover, the fact found in field was one discourse has more than one function.Methods and techniques used there are three. (1) Methods and techniques of data collection. The method used is the methods and techniques used refer to is the techniquesee, technical note, and interview techniques. (2) Methods and techniques of data analysis. The method used is the method match (match referential, translational, orthographic, and pragmatic. The basic technique used is the technique Segment Element Determinants (PUP) and subsequent techniques are Contacts Appeal of discernment (HBM). (3) Techniques and methods of presentation of the results of data analysis used, namely formal and informal methods.This study also resulted in a finding of speech acts, especially in terms of the function of speech. Apparently, the speech was not only contains the speech function, but more than one function of speech. Examples of speech it is data (1) not only contains the function to inform, but also insinuated, the data (2) not only inform, but also to express satisfaction, the data (3) not only inform but also revealeda complaint, the data (4) not only inform, but also in the form of a hope, and data (5) not only inform, but also banned. Keywords: speech acts, status, and facebook